Analisis Kebijakan Guru: Kebijakan P3K dan Guru Penggerak - Qomariyah, Eva; Duryat, Masduki (Sunan Kalijaga International Journal on Islamic Educational Research, 2024)
This article discusses three main aspects of education policy in Indonesia: education policy analysis, Government Employee with Work Agreement (PPPK) policy, and Teacher Mobilization policy. Education policy analysis is an intellectual and practical process that focuses on the creation, critical assessment, and communication of knowledge related to education policy to resolve various problems. Teachers have an important role in developing students' cognitive, affective and psychomotor aspects and function as facilitators, processors and educational planners. The PPPK policy aims to improve the welfare of honorary teachers by raising salary standards and providing more secure job status. However, this policy also has negative impacts such as a shortage of students in private schools due to the transfer of teachers to state schools. The Teacher Mobilization Program is designed to improve teacher competency through training that focuses on 21st century learning and Pancasila education. Mobilizing Teachers are expected to be agents of change in the education ecosystem, promoting innovation, creativity and student-centered learning. Through analysis of education policies, PPPK policies, and the Teacher Mobilization program, this article highlights the important role of teachers in education as well as the challenges and opportunities faced in efforts to improve the quality of education in Indonesia.